2011
DOI: 10.1186/1472-6963-11-336
|View full text |Cite
|
Sign up to set email alerts
|

Do we have the right models for scaling up health services to achieve the Millennium Development Goals?

Abstract: BackgroundThere is widespread agreement on the need for scaling up in the health sector to achieve the Millennium Development Goals (MDGs). But many countries are not on track to reach the MDG targets. The dominant approach used by global health initiatives promotes uniform interventions and targets, assuming that specific technical interventions tested in one country can be replicated across countries to rapidly expand coverage. Yet countries scale up health services and progress against the MDGs at very diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 13 publications
1
93
0
Order By: Relevance
“…We argue that such analysis is an important first step in assessing the potential contribution of SMS (and eHealth more broadly); a second step would be to select mHealth strategies that are worthy of scale as part of a strength, weakness, opportunities, and threats analysis or other strategies used by governments and implementing agencies to make these decisions. With such complexities identified and strategies in place to attempt to manage some complexities, robust monitoring and evaluating frameworks are needed to ensure that SMS investments effectively address identified challenges and equip key actors to handle existing and emerging complexity-capacities that are critical for sustaining and scaling up interventions in resource poor settings (Leon, Schneider, & Daviaud, 2012, Mair et al, 2012Paina & Peters, 2011;Subramanian, Naimoli, Matsubayashi, & Peters, 2011). To date, rigorous evaluation of programs using SMS technology has been limited, and further research in this area will be vital to ensure that potential benefits of mHealth innovations reduce health inequities and reach those most in need (Patil, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…We argue that such analysis is an important first step in assessing the potential contribution of SMS (and eHealth more broadly); a second step would be to select mHealth strategies that are worthy of scale as part of a strength, weakness, opportunities, and threats analysis or other strategies used by governments and implementing agencies to make these decisions. With such complexities identified and strategies in place to attempt to manage some complexities, robust monitoring and evaluating frameworks are needed to ensure that SMS investments effectively address identified challenges and equip key actors to handle existing and emerging complexity-capacities that are critical for sustaining and scaling up interventions in resource poor settings (Leon, Schneider, & Daviaud, 2012, Mair et al, 2012Paina & Peters, 2011;Subramanian, Naimoli, Matsubayashi, & Peters, 2011). To date, rigorous evaluation of programs using SMS technology has been limited, and further research in this area will be vital to ensure that potential benefits of mHealth innovations reduce health inequities and reach those most in need (Patil, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The results of these projects have been used to improve efficiencies in HIV care and testing, overcome barriers to access to care, and inform new health policies. In these ways, the Afya Bora Fellowship in Global Health used the kind of model suggested by Subramanian et al (2011), who contended that “learning by doing” was an effective method for health system change. The type of projects that Afya Bora fellows developed and implemented (Table 3) have been aligned to health system strengthening interventions that result in health impacts and outcomes in areas of improved service provision/quality, increased financial protection, increased service utilization, and uptake of healthy behaviors (USAID, 2015).…”
Section: Afya Bora Narrows Gaps In Leadership Trainingmentioning
confidence: 99%
“…As of 2014, the World Health Organization (WHO, 2014) reported that Africa was home to more than 60% of people living with HIV in the world and where 72% of HIV-related deaths occurred. For nations falling short of meeting MDGs, Subramanian, Naimoli, Matsubayashi, and Peters (2011) have questioned whether the right models were in place to scale-up interventions. They proposed a practical approach suggesting more promising inroads to coming up with solutions by “learning by doing” in ways that engage key stakeholders, use data to address constraints, and consider pilot or small scale projects to bring about needed changes in health care.…”
mentioning
confidence: 99%
“…The impact of health education on reproductive health knowledge among adolescents in a rural Nigerian community (Continued) We decided to use the WHO-ExpandNet framework because it broke down the model for scale up into pieces that could be examined closely and provided clear objective analysis criteria. However, based on our examination of other frameworks and the related literature, particularly two reviews published in 2011 (Yamey 2011;Subramanian et al 2011), we strengthened the WHO-ExpandNet framework in one area -the need to evaluate the innovation as scaling up occurs followed with responsive modifications in an ongoing manner. …”
Section: Analytic Frameworkmentioning
confidence: 99%